Induction of Strong Neutralization Antibodies in Mice after Inoculation with Dengue-2 Envelope DNA Vaccines - Pérez-Vélez, Mariel E.; García-Nieves, Teresita; Colón-Sánchez, Candimar; Martínez, Idalí (Puerto Rico Health Sciences Journal, 2009)
Background: Dengue (DEN) viruses have become a public health problem that affects approximately 100 million people worldwide each year. Prevention measures rely on vector control programs, which are inefficient. Therefore, a vaccine is urgently needed. Methods: The main goal of our group is to develop an efficient tetravalent DEN DNA vaccine. In this study, we constructed four DEN-2 DNA vaccines expressing prM/env genes, using the homologous leader sequence (VecD2, VRD2E) or the tissue plasminogen activator (tpa) secretory signal (VecD2tpa, VRD2tpa). In vitro expression was tested by transient transfections and western blot. The immunogenicity and protective efficacy of the vaccine candidates was evaluated in BALB/c mice, using two vaccination routes: intramuscular (IM) and intradermal (ID). Results: Envelope (E) protein expression was detected in transfected COS-7 or 293T cells. We found statistical differences in the antibody responses induced by these vaccine candidates. In addition, the strongest antibody responses and protection were observed when the vaccines were delivered intramuscularly. Moreover, the tpa leader sequence did not significantly improve the vaccine immunogenicity since VecD2 and VecD2tpa induced similar antibody responses. Conclusions: We demonstrated that most of our DNA vaccine candidates could induce antibody responses and partial protection against DEN-2 virus in mice. These results provide valuable information for the design and construction of a tetravalent DEN DNA vaccine.